Electrically and thermally conductive hydrophobic polymer composite film and preparation method and application thereof
By modifying silver nanoparticles on the surface of polyurethane nano -fiber and depositing multi -wall carbon nanotubes to build a composite film of the sandwich structure, the performance decline caused by conductive or thermal filler agglomeration has achieved low resistance, high thermal conductivity and hydrophobicity. Composite membrane.
Patent Information
- Application Number
- CN202411299194.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-18
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-09-18
AI Technical Summary
Conductive or thermally conductive fillers tend to accumulate during electrospinning, resulting in increased solution viscosity and decreased mechanical properties of fiber membranes.
By constructing a sandwich structure, spherical silver nanoparticles (AGNPS) are modified on the surface of polyurethane (PU) nanofiber, and then multi -wall carbon nanotuba (MWCNTS) is deposited on the upper and lower surfaces of nano fiber membranes, and interactions between the layer through the heat pressure increase layer Essence
The low resistance, high thermal guidance and good hydrophobicability of the composite membrane are available, suitable for thermal interface materials, and improved the mechanical properties of composite materials.
Smart Images

Figure CN119352287A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of functional polymer materials and relates to an electrically conductive and thermally conductive hydrophobic polymer composite film and a preparation method and application thereof. Background Art
[0002] Conductive and thermally conductive polymer fiber / fabric composites (CPFCs) have the characteristics of light weight, low cost, good flexibility and excellent air permeability. They are booming because of their potential application prospects in the field of flexible and wearable electronic products. The manufacture of CPFCs usually constructs a conductive and thermally conductive network inside the polymer fiber / fabric film. Hybrid electrospinning is a method for directly preparing conductive and thermally conductive polymer fiber composites. For example, by mixing polyimide (PI) with thermally conductive SiN to form a uniform solution, and then electrospinning, the thermally conductive SiN generates a complete thermally conductive network according to the arrangement of the fibers, while inheriting the excellent thermal stability, chemical resistance, radiation resistance and mechanical properties of the PI matrix. When the SiN content is 35wt.%, the heat transfer efficiency of a single fiber is increased by ~25% compared with pure PI fibers (Moradi, et al. Bridging agap in thermal conductivity and heat transfer in hybrid fibers and yarns viapolyimide and silicon nitride composites. Small, 2023, 19(52): 2305104.). However, when conductive or thermally conductive fillers are mixed in a solution for electrospinning, nanoparticles (especially at high concentrations) tend to aggregate, which not only greatly increases the viscosity of the solution and thus deteriorates the processing performance, but also easily leads to a decrease in the mechanical properties of the fiber membrane. In order to solve this problem, conductive and thermally conductive nanofillers are assembled on the fiber surface through interfacial interactions such as hydrogen bonding, electrostatic forces, and interfacial sintering. The resulting core-shell structure can maintain the good flexibility of the polymer fiber membrane, avoid the aggregation of conductive particles, and build a more effective conductive and thermally conductive network. For example, MXene nanosheets with rich functional groups (such as fluorine-containing groups) can be assembled on the fiber surface by dip coating. Conductive nanofillers without surface functional groups can also be modified on the fiber by ultrasound-assisted interfacial sintering. First, carbon nanomaterials such as reduced graphene oxide, carbon nanotubes, and carbon nanofibers are dispersed in a solvent, and then these rigid nanofillers are driven by an ultrasonic field to impact the soft nanofibers at high speed to produce interfacial bonding, and the nanofillers are fixed to the impacted part of the nanofibers.Ma et al. reported a method for preparing core / shell conductive nanofibers by impregnation. After coating multi-walled carbon nanotubes (MWCNTs) on the fiber surface, they further enhanced the interface interaction between the conductive shell and the internal fiber and MWCNTs by annealing. With the increase of MWCNTs content, the mechanical properties of the composite film also increased further, which was mainly due to the improvement of the interface interaction between the components inside the composite material. By adjusting the experimental conditions, the resistance of the obtained fiber can be controlled between 732 and 30Ω / sq (Ma, et al. Preparation of core / shell electrically conductive fibers by efficient coating carbon nanotubes on polyester. Advanced Fiber Materials, 2021, 3 (3): 180-91.). Whether it is surface assembly or sintering, the conductive shell layer wrapped around the polymer fiber is usually very thin, corresponding to a relatively low concentration of nanofillers, so the thermal conductivity and electrical conductivity are low. Summary of the invention
[0003] Technical problem to be solved: The present invention provides a conductive and thermally conductive hydrophobic polymer composite membrane, and a preparation method and application thereof. By constructing a sandwich structure, a composite membrane with excellent electrical conductivity, thermal conductivity and hydrophobicity is prepared. Spherical silver nanoparticles (AgNPs) are uniformly modified on the surface of polyurethane (PU) nanofibers. Subsequently, MWCNTs are deposited on the upper and lower surfaces of the nanofiber membrane and hot pressing is used to improve the interlayer interaction and the mechanical properties of the composite material. At this time, the composite membrane has lower resistance and higher thermal conductivity, and can be used in thermal interface materials. In addition, MWCNTs also give the composite membrane better hydrophobicity (water contact angle is 132.8°).
[0004] Technical solution: A method for preparing a conductive and thermally conductive hydrophobic polymer composite membrane, comprising the following steps: step 1, adding polyurethane (PU) to a mixture of tetrahydrofuran (THF) and N,N-dimethylformamide (DMF) as a spinning solution, wherein the mass fraction of PU is 10-15wt.% of the total mass, and the mass ratio of THF to DMF solution is 1:4, and a polymer nanofiber membrane is obtained by electrostatic spinning; step 2, drying the polymer nanofiber membrane to remove residual THF and DMF, and then immersing the polymer nanofiber membrane in a dopamine (DA) solution, and drying after immersion to obtain a composite material with a surface covered with polydopamine (PDA); step 3, immersing the composite material with a surface covered with PDA in an AgNO3 solution, and immersing the composite material in a C6H 12After AgNO3 is reduced by O6 solution, it is dried to obtain a conductive and thermally conductive polymer nanofiber composite membrane with AgNPs coated on the fiber surface; step 4, depositing a layer of multi-walled carbon nanotubes (MWCNTs) on the upper and lower surfaces of the conductive and thermally conductive polymer nanofiber composite membrane by filtration, followed by hot pressing to obtain a conductive and thermally conductive hydrophobic polymer composite membrane with a sandwich structure.
[0005] Preferably, in step 1, the spinning voltage is 15 kV, the liquid feeding rate is 2 mL / h, and the distance between the needle and the receiver is 12 cm.
[0006] Preferably, in step 2, the concentration of the DA solution is 2-4 mg / mL, the pH of the PDA solution is 8-8.5, the immersion treatment time is 6-8 hours, and the immersion treatment temperature is 40-45°C.
[0007] Preferably, in steps 2 and 3, the drying temperature is 30-60°C.
[0008] Preferably, in step 3, the concentration of the AgNO3 solution is 20 mg / mL, and the concentration of C6H 12 The concentration of O6 solution is 80 mg / mL, and the immersion time is 2-5 hours.
[0009] Preferably, in step 4, the diameter of the sand core used for filtration is 40 mm, MWCNTs are dispersed in a mixed solvent of ethanol and water, the volume ratio of ethanol to water is 1:1, the concentration of MWCNTs is 1 mg / mL, the hot pressing temperature is 60-120°C, and the hot pressing time is 15 min.
[0010] The above preparation method produces a conductive and thermally conductive hydrophobic polymer composite film.
[0011] Application of the above-mentioned electrically conductive and thermally conductive hydrophobic polymer composite film in the preparation of multifunctional electrically conductive and thermally conductive composite materials.
[0012] The present invention realizes the conductive and thermal conductive network by constructing the AgNPs network in the PU matrix through hydrogen bonds, and then attaches the MWCNTs to the upper and lower surfaces of the composite membrane through filtration and hot pressing to construct a sandwich structure, thereby forming a more complete conductive and thermal conductive network and giving it better hydrophobicity.
[0013] Beneficial effects: (1) The present invention combines metal ion adsorption and reduction, vacuum filtration and hot pressing technology to construct a unique sandwich structure, effectively reducing the interface thermal resistance and electrical resistance, and realizing the functionalization of the composite fiber membrane. The resistance is reduced to 14.8mΩ / sq, while the thermal conductivity reaches 7.9W(m·K) -1 The composite fiber membrane has good hydrophobicity, and its water contact angle reaches 132.8°.
[0014] (2) The present invention improves the interface strength between nanoparticles and polymer matrix through multiple interface interactions (interfacial hydrogen bonds and physical adhesion), thereby improving the surface stability and durability of the composite fiber membrane.
[0015] (3) The polymer composite film prepared by the present invention has excellent photothermal conversion and electrothermal conversion performance, and can achieve a rapid and stable temperature increase effect under a standard sunlight and a small voltage.
[0016] (4) The polymer composite film prepared by the present invention has strain sensing performance, and the resistance maintains a stable response effect under different tensile strains and stretching rates, and has potential application scenarios in strain sensing. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 Schematic diagram of the preparation process of polymer composite membrane.
[0018] Figure 2 Scanning electron microscope images of the composite membrane surface prepared in Comparative Example 1 (a), the dopamine-modified PU surface (b), the composite membrane surface prepared in Comparative Example 2 (c), and the composite membrane surface prepared in Example 1 (d).
[0019] Figure 3 The scanning electron microscope images of the cross section of the composite membrane prepared in comparative example 2 (a), the cross section of the composite membrane prepared in example 1 (b), and the element distribution diagram of the cross section of the composite membrane prepared in example 1 (c).
[0020] Figure 4 The stress-strain curves (a) of the polymer composite films prepared in Example 1, Comparative Example 2, Comparative Example 9, Comparative Example 10 and Comparative Example 11, the cyclic tensile curve (b) and the 1000-times loading-unloading fatigue resistance curve (c) of the composite film prepared in Example 1.
[0021] Figure 5 This is a resistance comparison chart of the polymer composite films prepared in Examples 1-3 and Comparative Examples 3-11.
[0022] Figure 6 It is a comparison chart of the thermal conductivity in the horizontal direction and the vertical direction of the polymer composite films prepared in Example 1, Example 2, Example 3, Comparative Example 1 and Comparative Example 2.
[0023] Figure 7 This is a comparison chart of the water contact angles of the polymer composite films prepared in Examples 1-3 and Comparative Examples 3-11.
[0024] Figure 8 This is a comparison chart of the light-to-heat conversion performance of the polymer composite films prepared in Example 1, Example 2, Example 3, Comparative Example 1 and Comparative Example 2 under standard sunlight.
[0025] Fig. 9 The cyclic heating and cooling curve (a), the heating curve for 1 h (b) and the comparison diagram of the photothermal conversion performance under different light intensities (c) of the polymer composite film prepared in Experimental Example 1.
[0026] Fig.10 The volt-ampere characteristic curve (a) of the polymer composite membrane prepared in Example 1, the temperature rise curve under different voltages (b) and the comparison diagram of the first and tenth temperature rise and fall cycles (c).
[0027] Fig.11 Self-cleaning performance (a) and photothermal deicing performance (b) of the polymer composite film prepared in Experimental Example 1.
[0028] Fig.12 The resistance response of the polymer composite film prepared in Example 1 under different strains (a), the resistance response under different stretching rates (b), the real-time detection curve of the resistance change of neck bending (c) and the real-time monitoring curve of the resistance change of elbow bending (d).
[0029] Fig.13 Schematic diagram of thermal interface material (a), comparison of the cooling effect of the polymer composite film prepared in Example 1 as a thermal interface material and a commercial heat pad as a thermal interface material or no thermal interface material on the chip (b), and temperature comparison diagram of different positions of the polymer composite films prepared in Experimental Examples 1, 2 and 3 when heated by a point heat source. DETAILED DESCRIPTION
[0030] The present invention will be further described below in conjunction with the accompanying drawings and specific embodiments. However, the selected embodiments are only used to illustrate the present invention and do not limit the scope of the present invention.
[0031] Example 1
[0032] (1) PU was added to a mixture of THF and DMF as a spinning solution, the mass fraction of PU was 15wt.% of the total mass, the mass fraction ratio of THF to DMF solution was 1:4, and the electrospinning parameters were set, the voltage was 15kV, the liquid feed rate was 2mL / h, and the distance from the needle to the collecting device was 12cm. The obtained fiber membrane was placed in a 60°C oven to dry and remove residual solvent. Dopamine hydrochloride was dissolved in water to prepare a 2mg / mL dopamine solution, and the pH was adjusted to 8.5. The above fiber membrane was placed in the dopamine solution, soaked for 6 hours, taken out and placed in a 60°C oven to dry for standby use. AgNO3 particles were dissolved in water to prepare a 20mg / mL AgNO3 solution, and the above dopamine-modified fiber membrane was placed in the AgNO3 solution. While stirring, an equal volume of 80mg / mL C6H 12O6 solution, react until the solution is clear after the addition, take it out and place it in a 60℃ oven for drying. Place the fiber membrane loaded with AgNPs on a 40mm sand core, and add 7mL of MWCNT (1mg / mL) ethanol / water solution on its upper and lower surfaces respectively, with a volume ratio of ethanol to water of 1:1, and then filter it. After the filtration is completed, place it in a 60℃ oven for drying. Control the temperature of the hydraulic press to 100℃ and the pressure to 10MPa, hydraulically press the composite fiber membrane for 15min, then adjust the pressure of the flat vulcanizer to 15MPa, and compress it at room temperature for 2min. The preparation process is as follows Figure 1 The microstructure of the composite material is shown in Figure 2 and Figure 3 shown.
[0033] (2) Mechanical properties test:
[0034] The samples were cut into dumbbell-shaped specimens with a length of 50 mm and a neck width of 4 mm using a cutter. The samples were stretched at a rate of 50 mm / min by a universal testing machine until they broke, in order to determine the strength and elongation at break of different samples. Each sample was tested at least 5 times. In addition, the samples were subjected to a fixed strain cyclic loading test using a fatigue tensile machine, such as Figure 4 shown.
[0035] (3) Conductivity test:
[0036] The square resistance of the polymer composite film was tested using an RTS-9 four-probe tester. The test results are shown in Figure 5 As shown, the resistance of the polymer composite film reaches 14.8 mΩ / sq.
[0037] (4) Thermal conductivity test:
[0038] The LFA 467 thermal conductivity tester was used to test the thermal conductivity, thermal diffusivity and thermal diffusivity in the vertical direction of the polymer composite membrane, and the thermal conductivity in the horizontal direction of the polymer nanofiber composite membrane was calculated. The test results are shown in Figure 6 As shown, the thermal conductivity in the vertical direction reaches 0.9W (m·K) -1 , the horizontal thermal conductivity reaches 7.9W (m·K) -1 .
[0039] (5) Hydrophobicity test:
[0040] The water contact angle of the polymer composite film was tested using a contact angle meter. The test results are as follows: Figure 7 As shown, the water contact angle of the polymer composite film reaches 132.8°.
[0041] (6) Photothermal conversion performance test:
[0042] Using a xenon lamp to simulate standard sunlight intensity, the test results are as follows Figure 8 and Fig. 9 As shown, the polymer composite film can rise to about 45°C under one standard sun.
[0043] (7) Electrothermal conversion performance test:
[0044] A small voltage is applied to both ends of the polymer composite membrane, and the test results are as follows Fig.10 As shown, the composite film can heat up rapidly and stably at low voltage.
[0045] (8) Self-cleaning performance test:
[0046] Tilt the polymer composite film and sprinkle some sand and dust, and water drops will naturally fall onto the surface of the polymer composite film. The test results are as follows: Fig.11 As shown, dust is removed after water flows through the composite membrane.
[0047] (9) Photothermal deicing performance test:
[0048] Adjust the xenon lamp to simulate a standard sunlight, place the polymer composite film under the light source, and observe the melting time of the ice on the polymer composite film. The test results are as follows: Fig.11 As shown, the composite membrane can effectively shorten the melting time of ice cubes, and its hydrophobicity prevents water from penetrating into the composite membrane.
[0049] (10) Strain sensing performance test:
[0050] The composite film is pasted on the joints of the human body to detect human body movements in real time. The test results are as follows Fig.12 As shown, the composite membrane can respond quickly and stably to human body movements.
[0051] (11) Cooling test:
[0052] The polymer composite film is placed between the heat-generating chip and the heat sink as a thermal interface material. An infrared imager is used to record the temperature changes on the chip surface during the chip heating process. The test results are as follows: Fig.13 As shown, the composite film effectively transfers heat to the heat sink to reduce the chip temperature.
[0053] Example 2
[0054] (1) The preparation of the polymer composite membrane is basically the same as in Example 1, except that the volume of the MWCNT suspension used for filtration is 5 mL.
[0055] (2) Mechanical properties test:
[0056] Use a cutter to cut the sample into dumbbell-shaped specimens with a length of 50 mm and a neck width of 4 mm. Use a universal testing machine to stretch the sample at a rate of 50 mm / min until it breaks, so as to determine the strength and elongation at break of different samples. Each sample should be tested at least 5 times. Figure 4 shown.
[0057] (3) Conductivity test:
[0058] The square resistance of the polymer composite film was tested using an RTS-9 four-probe tester. The test results are shown in Figure 5 As shown, the resistance of the polymer composite film reaches 30 mΩ / sq.
[0059] (4) Thermal conductivity test:
[0060] The LFA 467 thermal conductivity tester was used to test the thermal conductivity, thermal diffusivity and thermal diffusivity in the vertical direction of the polymer composite membrane, and the thermal conductivity in the horizontal direction of the polymer nanofiber composite membrane was calculated. The test results are shown in Figure 6 As shown, the thermal conductivity in the vertical direction reaches 0.4W (m·K) -1 , the horizontal thermal conductivity reaches 3.6W (m·K) -1 .
[0061] (5) Hydrophobicity test:
[0062] The water contact angle of the polymer composite film was tested using a contact angle meter. The test results are as follows: Figure 7 As shown, the water contact angle of the polymer composite film reaches 128.1°.
[0063] (6) Photothermal conversion performance test:
[0064] Using a xenon lamp to simulate standard sunlight intensity, the test results are as follows Figure 8 As shown, the polymer composite film can rise to about 40°C under one standard sun.
[0065] Example 3
[0066] (1) The preparation of the polymer nanofiber composite membrane is basically the same as in Example 1, except that the volume of the MWCNT suspension used for filtration is 3 mL.
[0067] (2) Mechanical properties test:
[0068] Use a cutter to cut the sample into dumbbell-shaped specimens with a length of 50 mm and a neck width of 4 mm. Use a universal testing machine to stretch the sample at a rate of 50 mm / min until it breaks, so as to determine the strength and elongation at break of different samples. Each sample should be tested at least 5 times. Figure 4 shown.
[0069] (3) Conductivity test:
[0070] The square resistance of the polymer composite film was tested using an RTS-9 four-probe tester. The test results are shown in Figure 5 As shown, the resistance of the polymer composite film reaches 36.3 mΩ / sq.
[0071] (4) Thermal conductivity test:
[0072] The LFA 467 thermal conductivity tester was used to test the thermal conductivity, thermal diffusivity and thermal diffusivity in the vertical direction of the polymer composite membrane, and the thermal conductivity in the horizontal direction of the polymer nanofiber composite membrane was calculated. The test results are shown in Figure 6 As shown, the thermal conductivity in the vertical direction reaches 0.3W (m·K) -1 , the horizontal thermal conductivity reaches 3.3W (m·K) -1 .
[0073] (5) Hydrophobicity test:
[0074] The water contact angle of the polymer composite film was tested using a contact angle meter. The test results are as follows: Figure 7 As shown, the water contact angle of the polymer composite film reaches 129.6°.
[0075] (6) Photothermal conversion performance test:
[0076] Using a xenon lamp to simulate standard sunlight intensity, the test results are as follows Figure 8 As shown, the polymer composite film can rise to about 37°C under one standard sun.
[0077] Comparative Example 1
[0078] PU was added to a mixture of THF and DMF as a spinning solution, the mass fraction of PU was 15wt.% of the total mass, the mass fraction ratio of THF to DMF solution was 1:4, and the electrospinning parameters were set to a voltage of 15kV, a liquid feed rate of 2mL / h, and a distance of 12cm from the needle to the collecting device. The obtained fiber membrane was placed in an oven at 60°C to dry to remove residual solvent.
[0079] After the light-to-heat conversion performance test and thermal conductivity test, the test results are as follows Figure 6 and Figure 8 As shown, the polymer fiber membrane only rises to about 20°C under one standard sun, and the thermal conductivity is only 2.2 W (m·K). -1 , cannot meet the needs of light-to-heat conversion and thermal conductivity.
[0080] Comparative Example 2
[0081] PU was added to a mixture of THF and DMF as a spinning solution. The mass fraction of PU was 15wt.% of the total mass, and the mass fraction ratio of THF to DMF solution was 1:4. The electrospinning parameters were set, the voltage was 15kV, the liquid feed rate was 2mL / h, and the distance from the needle to the collecting device was 12cm. The obtained fiber membrane was placed in a 60°C oven to dry and remove residual solvent. Dopamine hydrochloride was dissolved in water to prepare a 2mg / mL dopamine solution, and the pH was adjusted to 8.5. The above fiber membrane was placed in the dopamine solution, soaked for 6 hours, taken out and placed in a 60°C oven for drying for standby use. AgNO3 was dissolved in water to prepare a 20mg / mL AgNO3 solution, and the above fiber membrane was placed in the AgNO3 solution. While stirring, an equal volume of 80mg / mL C6H 12 After the addition of O6 solution is completed, react until the solution is clear, take it out and place it in a 60℃ oven to dry.
[0082] After mechanical properties test, thermal conductivity test and light-to-heat conversion performance test, the test results are as follows Figure 4 , Figure 6 and Figure 8 As shown, the elongation at break and strength of the polymer fiber membrane are both low, rising only to about 22°C under a standard sunlight, and the thermal conductivity is only 3.1 W (m·K). -1 .
[0083] Comparative Example 3
[0084] The preparation of the polymer composite membrane is basically the same as in Example 1, except that the volume of the MWCNT suspension used for filtration is 3 mL and the hot pressing temperature is 60°C.
[0085] After conductivity test and hydrophobicity test, the test results are as follows Figure 5 and Figure 7 As shown, the resistance and water contact angle reach 55.3mΩ / sq and 128.1° respectively.
[0086] Comparative Example 4
[0087] The preparation of the polymer composite membrane is basically the same as in Example 1, except that the volume of the MWCNT suspension used for filtration is 3 mL and the hot pressing temperature is 80°C.
[0088] After conductivity test and hydrophobicity test, the test results are as follows Figure 5 and Figure 7 As shown, the resistance and water contact angle reach 40.3 mΩ / sq and 132.5° respectively.
[0089] Comparative Example 5
[0090] The preparation of the polymer composite membrane is basically the same as in Example 1, except that the volume of the MWCNT suspension used for filtration is 3 mL and the hot pressing temperature is 120°C.
[0091] After conductivity test and hydrophobicity test, the test results are as follows Figure 5 and Figure 7 As shown, the resistance and water contact angle reach 78.7 mΩ / sq and 120.5° respectively.
[0092] Comparative Example 6
[0093] The preparation of the polymer composite membrane is basically the same as in Example 1, except that the volume of the MWCNT suspension used for filtration is 5 mL and the hot pressing temperature is 60°C.
[0094] After conductivity test and hydrophobicity test, the test results are as follows Figure 5 and Figure 7 As shown, the resistance and water contact angle reach 43.3mΩ / sq and 126.9° respectively.
[0095] Comparative Example 7
[0096] The preparation of the polymer composite membrane is basically the same as in Example 1, except that the volume of the MWCNT suspension used for filtration is 5 mL and the hot pressing temperature is 80°C.
[0097] After conductivity test and hydrophobicity test, the test results are as follows Figure 5 and Figure 7 As shown, the resistance and water contact angle reach 37.3mΩ / sq and 136.3° respectively.
[0098] Comparative Example 8
[0099] The preparation of the polymer composite membrane is basically the same as in Example 1, except that the volume of the MWCNT suspension used for filtration is 5 mL and the hot pressing temperature is 120°C.
[0100] After conductivity test and hydrophobicity test, the test results are as follows Figure 5 and Figure 7 As shown, the resistance and water contact angle reach 52.3mΩ / sq and 121.8° respectively.
[0101] Comparative Example 9
[0102] The preparation of the polymer composite membrane is basically the same as in Example 1, except that the volume of the MWCNT suspension used for filtration is 7 mL and the hot pressing temperature is 60°C.
[0103] After conductivity test and hydrophobicity test, the test results are as follows Figure 5 and Figure 7 As shown, the resistance and water contact angle reach 23.8mΩ / sq and 123.8° respectively.
[0104] Comparative Example 10
[0105] The preparation of the polymer composite membrane is basically the same as in Example 1, except that the volume of the MWCNT suspension used for filtration is 7 mL and the hot pressing temperature is 80°C.
[0106] After conductivity test and hydrophobicity test, the test results are as follows Figure 5 and Figure 7 As shown, the resistance and water contact angle reach 18.3mΩ / sq and 136.4° respectively.
[0107] Comparative Example 11
[0108] The preparation of the polymer composite membrane is basically the same as in Example 1, except that the volume of the MWCNT suspension used for filtration is 7 mL and the hot pressing temperature is 120°C.
[0109] After conductivity test and hydrophobicity test, the test results are as follows Figure 5 and Figure 7 As shown, the resistance and water contact angle reach 32mΩ / sq and 132.9° respectively.
[0110] The above examples are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with the technology to understand the content of the present invention and implement it accordingly, and they cannot be used to limit the protection scope of the present invention. Any equivalent transformation or modification made according to the spirit of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a conductive and thermally conductive hydrophobic polymer composite film, characterized in that: The following steps are involved: Step 1, adding polyurethane (PU) to a mixture of tetrahydrofuran (THF) and N,N-dimethylformamide (DMF) as a spinning solution, the mass fraction of PU is 10-15 wt.% of the total mass, the mass ratio of THF to DMF solution is 1:4, and a polymer nanofiber membrane is obtained by electrospinning; Step 2, drying the polymer nanofiber membrane to remove residual THF and DMF, soaking it in a dopamine (DA) solution, and drying it after the soaking to obtain a composite material with a surface covered with polydopamine (PDA); Step 3, soaking the composite material with a surface covered with PDA in an AgNO3 solution, and spinning it by C6H 12 After AgNO3 is reduced by O6 solution, it is dried to obtain a conductive and thermally conductive polymer nanofiber composite membrane with AgNPs coated on the fiber surface; step 4, depositing a layer of multi-walled carbon nanotubes (MWCNTs) on the upper and lower surfaces of the conductive and thermally conductive polymer nanofiber composite membrane by filtration, followed by hot pressing to obtain a conductive and thermally conductive hydrophobic polymer composite membrane with a sandwich structure.
2. The preparation method according to claim 1, characterized in that: In step 1, the spinning voltage was 15 kV, the liquid feeding rate was 2 mL / h, and the distance between the needle and the receiver was 12 cm.
3. The preparation method according to claim 1, characterized in that: In step 2, the concentration of the DA solution is 2-4 mg / mL, the pH of the PDA solution is 8-8.5, the soaking treatment time is 6-8 hours, and the soaking treatment temperature is 40-45°C.
4. The preparation method according to claim 1, characterized in that: In steps 2 and 3, the drying temperature is 30-60°C.
5. The preparation method according to claim 1, characterized in that: In step 3, the concentration of AgNO3 solution is 20 mg / mL, and C6H 12 The concentration of O6 solution is 80 mg / mL, and the immersion time is 2-5 hours.
6. The preparation method according to claim 1, characterized in that: In step 4, the diameter of the sand core used for filtration is 40 mm, MWCNTs are dispersed in a mixed solvent of ethanol and water, the volume ratio of ethanol to water is 1:1, the concentration of MWCNTs is 1 mg / mL, the hot pressing temperature is 60-120 °C, and the hot pressing time is 15 min.
7. The electrically conductive and thermally conductive hydrophobic polymer composite film prepared by the preparation method according to any one of claims 1 to 6.
8. Use of the electrically conductive and thermally conductive hydrophobic polymer composite film according to claim 7 in the preparation of a multifunctional electrically conductive and thermally conductive composite material.
Citation Information
Patent Citations
Composite fiber membrane with asymmetric wettability, preparation method of composite fiber membrane and application of composite fiber membrane in oil-water separation
CN114247312A
Preparation method of double-conductive-network super-hydrophobic fabric strain sensor
CN115748241A
Breathable polymer nanofiber composite membrane with high electric conductivity and heat conductivity as well as preparation method and application of breathable polymer nanofiber composite membrane
CN118007411A
Flexible super-hydrophobic high-absorption electromagnetic shielding composite film based on multilayer structure and preparation method of flexible super-hydrophobic high-absorption electromagnetic shielding composite film
CN118110028A
Fiber membrane with waterproof, antibacterial and electromagnetic shielding functions and preparation method and application thereof
CN118441469A
Cited By
Breathable polymer nanofiber composite membrane with high electric conductivity and heat conductivity as well as preparation method and application of breathable polymer nanofiber composite membrane
CN118007411A
Self-sensing and self-heating basalt fiber composite material and preparation method thereof
CN119898084A
Preparation process and application of polyimide nanofiber membrane
CN119980684A